The impact of delayed ventilation tube insertion in otitis media with effusion on children's development - Özgur Akdoğan; Gülşen Erdem; Hasan Nedim Arda; Mehmet Ali Çetin; Sermet Akkuş; Arif Nadi Arda (Turkish Archives of Otorhinolaryngology, 2006)

(untitled)
Objectives: The effect of delayed ventilation tube insertion in children concerning linguistic, speech and cognitive development with otitis media with effusion (OME) were examined in this study.Methods: Randomized controlled trial. Wechsler Intelligence Scale for Children - Revised and Peabody Picture Vocabulary Tests were applied two groups of children. Study group consists of the children with OME who had ventilation tube insertion delayed for nine or more months control group with OME who had ventilation tube insertion before nine months.Results: Significant statistical difference have been found out between these two groups in the parameters such as total intelligence, verbal intelligence, receptive language, general information, comprehension, arithmetic, similarity, vocabulary, picture completion and picture arrangement. The control group has been found more successful in these tests according to the group with children who had OME surgery after nine months. However, in the parameters of design with cubes, coding and object assembling, no significant difference has been found out between the two groups.Conclusion: Delayed tube insertion in OME has a permanent negative effect on children’s articulation, linguistic and cognitive development. For this reason, following OME diagnosis, hearing loss in children should be followed at regular intervals by audiological tests and if hearing loss is not improving for more than nine months ventilation tube should be inserted immediately.